UNIQUE MEDICINAL PLANTS OF THE SHOHIMARDONSOY BASIN, THEIR PROTECTION (Scientific journal of the Fergana State University, 2024)
The article contains information about rare and valuable medicinal plants in the Shahimardonsoy region. The importance of preserving the unique endemic species included in the Red Book of the Republic of Uzbekistan, especially the Aloy's Ivy and the Margarita Marmaragi, is emphasized.